2006
DOI: 10.1002/cta.356
|View full text |Cite
|
Sign up to set email alerts
|

On the realization of current transfer function using voltage amplifiers

Abstract: Current transfer function is a feature of current‐mode filters. Current‐mode filters have so far been realized principally using current amplifiers and current conveyors. Some current‐mode filter architecture using operational amplifiers have also been reported. In this article it is shown that by using the principles of transposed network and nullor model for the active device, a current transfer function can be realized in a very simple way using a voltage amplifier, i.e. operational amplifier (OA). The key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Furthermore, the application of this technique to current mode configurations is straightforward and could be realized to take advantage of current mode operation [19].…”
Section: R-2r Mcd-based Pgamentioning
confidence: 99%
“…Furthermore, the application of this technique to current mode configurations is straightforward and could be realized to take advantage of current mode operation [19].…”
Section: R-2r Mcd-based Pgamentioning
confidence: 99%
“…Much research has been devoted to the realization of current-mode (CM) filters [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] employing various active devices because of their versatility and convenience for practical usages in many areas, such as communication systems and signal processing. Thus, a number of CM filter designs are proposed in the literature employing operational amplifiers (OAs) [1], current conveyors (CCs) 740 E. YUCE, A. KIRCAY AND S. TOKAT [2][3][4][5][6][7][8] and second-generation current-controlled conveyors (CCCIIs) [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a number of CM filter designs are proposed in the literature employing operational amplifiers (OAs) [1], current conveyors (CCs) 740 E. YUCE, A. KIRCAY AND S. TOKAT [2][3][4][5][6][7][8] and second-generation current-controlled conveyors (CCCIIs) [9][10][11][12][13][14][15][16][17]. On the other hand, it is stated in [18,19] that CM operations have better properties, such as greater linearity, lower power consumption, wider bandwidth and larger dynamic range than their voltage-mode (VM) counterparts, for example, OAs.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article [7], the authors have briefly reported on this concept. In this article, we shall elaborate on the application of the principles of nullor and transposed networks for the realization of a CM filter from a given VM realization.…”
Section: Introductionmentioning
confidence: 99%